Organotin levels in Nazare canyon (west Iberian Margin, NE Atlantic) and adjacent coastal area - Sousa, Ana C. A. (2012)
Organotin compounds (OTs) are ubiquitous in the marine environment and high concentrations (mu g g(-1) range) in sediments from different coastal areas around the world have been reported. However, few reports have described the OTs contamination status in the offshore and deep sea environment. This work investigated organotin levels in Nazare canyon for the first time. Levels of monobutyltin (MBT), dibutyltin (DBT), tributyltin (TBT), diphenyltin (DPT), triphenyltin (TPT), dioctyltin (DOT) and trioctyltin (TOT) were quantified in sediment samples from the upper flanks of the canyon and from the adjacent coastal area. TBT levels detected in the canyon flanks are about two to three orders of magnitude lower than those found in the coastal area. Nevertheless, when quantifiable. TBT levels in the canyon samples were higher than the Environmental Assessment Criteria set for TBT in sediments by the OSPAR Commission indicating that at those locations negative ecological impacts are likely to occur. (C) 2011 Elsevier Ltd. All rights reserved.